Research progress on effects of traditional Chinese medicine on myocardial ischemia–reperfusion injury: A review - Xing, Na; Long, Xiao-Tong; Zhang, Hui-Juan; Fu, Li-Dan; Huang, Jian-Yuan; Chaurembo, Abdallah Iddy; Chanda, Francis; Xu, Yun-Jing; Shu, Chi; Lin, Kai-Xuan; Yang, Ke; Lin, Han-Bin (Frontiers in Pharmacology, 2022)
Ischemic heart disease (IHD) is a high-risk disease in the middle-aged and elderly population. The ischemic heart can be further damaged after reperfusion therapy with percutaneous coronary intervention (PCI) and other methods, namely myocardial ischemia-reperfusion injury (MIRI), which further affects revascularization and hinders patient rehabilitation. Therefore, investigating new therapies for MIRI has drawn much global attention. With a long history in the prevention and treatment of MIRI, the scientific community has increasingly recognized traditional Chinese medicine (TCM) for its multi-component and multi-target effects. These multi-target effects provide a conspicuous advantage to anti-MIRI of TCM to overcome the shortcomings of the single component drugs, thereby pointing toward a novel avenue for treatment of MIRI. However, very few reviews had summarized the currently available anti-MIRI of TCM. Therefore, a systematic data mining of TCM for protecting against MIRI will certainly accelerate the processes of drug discovery and help to identify safe candidates with synergistic formulations. The present review aims to describe TCM-based research in MIRI treatment through electronic retrieval and articles, patents, and ethnopharmacology documents. This review reported the progress of research on active ingredients, efficacy, and underlying mechanism of anti-MIRI of TCM and TCM formulas provided scientific support to the clinical use of TCM in the treatment of MIRI, and revealed its corresponding clinical significance and development prospects of TCM treatment of MIRI.